Topical N-acetylcysteine treatment in neonatal ichthyosis - Sarici, S Umit; Sahin, Murat; Yurdakök, Murat (The Turkish Journal of Pediatrics, 2003)
Unpredictable trancutaneous absorption of topically administered drugs and potential teratogenicity and toxicity of systemic drugs would make it mandatory to innovate more efficacious and less toxic drugs for the treatment of ichthyosis, which is not a fully curable disease in the neonatal period. In this article the clinical efficacy of 10% N-acetylcysteine emulsion in the topical treatment of congenital ichthyosis in a newborn was assessed, comparing simultaneously with 4% urea emulsion. After treating the skin of the left and right halves of the body with topical N-acetylcysteine and 4% urea, respectively, for nine days, the improvement was much more outstanding on the skin of the left half of the body when compared to the right half of the body. Topical N-acetylcysteine, to our knowledge, has not been used in a newborn with ichthyosis before, and this is the first report of a case of neonatal ichthyosis successfully treated with topical N-acetylcysteine. We conclude that 10% N-acetylcysteine emulsion, as an non-toxic and hypoallergic amino acid derivative, can be safely and efficaciously used in the topical treatment of neonatal ichthyosis, although the permanent cure may not always be possible.